2017
DOI: 10.18632/oncotarget.20016
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic circulating tumor DNA quantificaton for the individualization of non-small-cell lung cancer patients treatment

Abstract: BackgroundLiquid biopsy has evolved from being a promising line to becoming a validated approach for biomarker testing. However, its utility for individualization of therapy has been scarcely reported. In this study, we show how monitoring levels of EGFR mutation in plasma can be useful for the individualization of treatment.ResultsLongitudinal EGFR mutation levels in plasma always correlated with tumor response ascertained by RECIST criteria. Moreover, decreasing EGFR mutation levels were detected in all pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Treatment response has been monitored by observing the abundance of known driver mutations, where the fluctuations of EGFR-mutant abundance in the serial plasma cfDNA samples are in accordance with the changes in tumor size assessed via imaging scans ( 60 ). In addition, longitudinal EGFR mutation levels in plasma correlated with the tumor response determined using RECIST criteria ( 12 ). In 19 patients treated with afatinib for ≥24 weeks, the number of EGFR mutant alleles detected in cfDNA via digital polymerase chain reaction (PCR) declined rapidly and markedly after treatment onset, becoming undetectable or detectable at only a low copy number (<10 copies per milliliter) at 4 weeks ( 23 ).…”
Section: Current Role Of Liquid Biopsies In Deciding the Treatment Fomentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment response has been monitored by observing the abundance of known driver mutations, where the fluctuations of EGFR-mutant abundance in the serial plasma cfDNA samples are in accordance with the changes in tumor size assessed via imaging scans ( 60 ). In addition, longitudinal EGFR mutation levels in plasma correlated with the tumor response determined using RECIST criteria ( 12 ). In 19 patients treated with afatinib for ≥24 weeks, the number of EGFR mutant alleles detected in cfDNA via digital polymerase chain reaction (PCR) declined rapidly and markedly after treatment onset, becoming undetectable or detectable at only a low copy number (<10 copies per milliliter) at 4 weeks ( 23 ).…”
Section: Current Role Of Liquid Biopsies In Deciding the Treatment Fomentioning
confidence: 99%
“…In addition, early progression as indicated by T790M mutation in plasma can be detected earlier than that detected in computed tomography (CT) scans. In a study of 41 patients, progression was detected from plasma samples 51 days prior to those detected in CT scans ( 12 ). Another study that enrolled 102 patients even reported an earlier detection time of 103 days ( 66 ).…”
Section: Current Role Of Liquid Biopsies In Deciding the Treatment Fomentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, if ctDNA is present after curative treatment, the risk of relapse is significantly increased (Garcia‐Murillas et al , ). Likewise, an increase in the concentration of ctDNA during ongoing treatment precedes disease progression (Demuth et al , ; Provencio et al , ; Xiong et al , ). These findings offer new hope for monitoring disease activity using ctDNA and emphasise how ctDNA may be a valuable tool in the treatment–decision pathway in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…cfDNA profiling has proved to be useful to guide personalized treatments based on the molecular profile, for early detection of resistance mechanisms [35,36], early detection of disease recurrences, as well as tumor response to therapy monitoring [37] by means of sequential liquid biopsies. Furthermore, several studies comparing the detection of EML4-ALK translocation by formalin-fixed paraffinembedded (FFPE) tissuesand liquidbiopsy havereportedthat indeed cfDNA can be used as a surrogate of FFPE DNA [38].…”
Section: Liquid Biopsymentioning
confidence: 99%